Evaluation of the anterior cervical angle of the uterus to predict spontaneous preterm birth - Sur, Bijay; Misra, Sujata; Dash, Sanghamitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This prospective observational study was conducted to evaluate the anterior cervical angle (ACA) of the uterus by transvaginal sonography (TVS) and to determine the feasibility to predict spontaneous preterm birth (PTB). The duration of the study was from December 2014-December 2016.The participants included 100 pregnant women with singleton pregnancy who were asymptomatic. They were enrolled after excluding all known risk factors of preterm birth. Methods: The ACA and cervical length were measured in all cases by transvaginal sonography either in the 1st trimester or 2nd trimester. All cases were followed and well documented with respect to the gestational age at delivery. Results: There was a significant risk of preterm labour in women with cervical length <2.5cm in the 2nd trimester with Odds Ratio 3.625, P value=0.001, sensitivity 75% and specificity 79.31%. The positive predictive value was 33.33% and negative predictive value 95.83%. The false positive rate was 20.65% and false negative rate 25%. The difference of mean cervical angle in women who delivered preterm and that of those who delivered at term, in the 1st trimester (preterm group 114.2°Vs term group 93.0°, P<0.001) and in the 2nd trimester (preterm group 127.66° Vs term group 103.65°, P <0.001) was significant. An ACA of 114.2° in the 1st trimester was associated with a risk of spontaneous preterm birth (P value 0.0065, sensitivity 90% and specificity 80%). An ACA of 127.66° in 2nd trimester was associated with a risk of spontaneous preterm birth (P value 0.0004, sensitivity 80%and specificity 88.23%). Conclusions: Despite the limitations of a small sample size, the results suggest that the anterior cervical angle has potential as a new predictor of spontaneous preterm birth especially when measured in the 1st trimester.